2017
DOI: 10.3892/ol.2017.6487
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell chymase affects the proliferation and metastasis of lung carcinoma cells in vitro

Abstract: Abstract. Metastasis of lung carcinoma cells is a major cause of organ failure and mortality of patients with lung cancer. Lung mast cells are a type of immune cell which reside in the respiratory mucosa. High numbers of mast cells are associated with the majority of common types of cancer; however, the effects of mast cells on cancer remain unclear. In the present study, the effects of mast cell chymase (MCC) on the proliferation and adhesion of the lung carcinoma cell lines A549 and H520 was investigated. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…MC chymase Dose-dependent chymase decreased the rate of proliferation of both cell lines after 24 h post treating. It also hampered the A549 cells adhesion ability, downregulated the expression of E-cadherin [33] Glioma cell lines U2987MG and U3086MG…”
Section: Cells Of the Adaptive Immune System In Tmementioning
confidence: 99%
See 1 more Smart Citation
“…MC chymase Dose-dependent chymase decreased the rate of proliferation of both cell lines after 24 h post treating. It also hampered the A549 cells adhesion ability, downregulated the expression of E-cadherin [33] Glioma cell lines U2987MG and U3086MG…”
Section: Cells Of the Adaptive Immune System In Tmementioning
confidence: 99%
“…It is also reported that chymase increases the expression of MMP-9 in tumor cells. Chymase therefore promotes the separation, proliferation, and relocation of cell clusters through acting directly and indirectly on ECM to support metastasis [33].…”
Section: And Extracellular Matrix During Tumor Developmentmentioning
confidence: 99%
“…27 Studies conducted on mast cells containing chymase have led to the conclusion that chymase may be associated with tumor cell proliferation and metastasis. 43 In this study, mast cell distribution containing chymase was found to be mostly intratumoral (P=0.007). It is thought to be associated with tumor progression.…”
mentioning
confidence: 49%
“…In conclusion, recent studies appear to suggest that MCT and MCTC may represent a promising target in cancer treatment due to its proangiogenic activity. [43][44][45] However, the character of MCT and MCTC expression in cancer types needs to be understood better. In our study, MCT expression in prostate carcinoma (intratumoral areas and peritumoral areas) were observed to be higher.…”
mentioning
confidence: 99%
“…Furthermore, tumor sections from 32 cases of adenocarcinoma and 13 cases of squamous cell carcinoma revealed significantly higher counts of chymase-positive mast cells in the central region than those in the normal regions [28]. Chymase has been associated with TGF-β activation and endothelin-1 formation from preproendothelin-1 in pulmonary fibrosis and chronic obstructive pulmonary disease [26], and in proliferation, adhesion, regulation of E-cadherin expression, and modulation of immunosuppressive microenvironment in lung carcinoma [29,30]. This effect is likely due to TGF-β inhibitory effect on T-cell proliferation and effector activity.…”
Section: Introductionmentioning
confidence: 99%